Исследование собственных частот лопастей рабочих колес ПЛ-60 в воздухе и воде - Линник, Александр Васильевич; Душин, Алексей Викторович (НТУ "ХПИ", 2017)
Определены собственные частоты лопастей семилопастных рабочих колес ПЛ-60, выявлено влияние различных факторов на величины их собственных частот. Выполнен пересчет собственных частот лопастей модельного рабочего колеса на параметры натурного рабочего колеса. Проведен сравнительный анализ экспериментальных собственных частот с собственными частотами, определенными для математической модели лопастей. Получены коэффициенты снижения собственных частот в воде для лопастей рабочих колес ПЛ-60/1075 и ПЛ-60/3160.

Blade natural frequencies are determined for seven-blade Kaplan runners ПЛ-60, the influence of various factors on the blade natural frequency values is explored. The model runner blade natural frequencies are scaled up to the prototype runner conditions. A mathematical model is designed to determine natural frequencies by the FEM method for flat shells as well as for elastic solids. A comparative analysis is conducted for experimental natural frequencies and natural frequencies as determined for the mathematical model of the blades. Coefficients of natural frequency reduction in the water are obtained for runners ПЛ-60/1075 and ПЛ-60/3160. The experiment results obtained are of high value in the resolution of the issue of numerical analysis reliability.
Study of natural blade frequencies of runners PL-60 in the air and in the water
Keywords: гидротурбины; модельне испытания; эксперимент; метод конечных элементов; математическая модель; runner blade; hydraulic turbines; model tests; experiment; natural frequencies; finite element method; mathematical model